Women of the Bible : from text to image - Seijas de Los Ríos-Zarzosa, María Guadalupe; Walker-Vadillo, Monica Ann (London ; New York : T&T Clark, 2022)
"The contributors present an interdisciplinary approach to the representations of women in the Hebrew Bible by focusing on texts, images and gender"--
Bible, art and women: criteria for analysis and critical interpretation / Carmen Yebra-Rovire -- The iconographic representation of the Bible: the interaction between text and image / Guadalupe Seijas -- Bathsheba in medieval manuscripts: visual analysis of a controversial Old Testament woman / Mónica Ann Walker Vadillo -- Strong women of the Bible and their persistence in seventeenth-century Spanish painting / Amparo Alba Cecilia, Guadalupe Seijas -- Moses's mother and her literary and visual reception in the nineteenth century / Carmen Yebra-Rovira -- The women in the book of Judges and their representation in nineteenth-century engravings / Carmen Yebra-Rovira -- Ruth and Naomi: a story of friendship in images / Guadalupe Seijas.
This English version presents edited versions of the five chapters of the revised and updated Spanish version, published in 2015 and incorporates two new ones (chapters 2 and 5), expanding the iconographic analysis to the New Testament with the representation of Mary Magdalene ... .
Includes bibliographical references and indexes.
Translated from the Spanish.
Keywords: Women in the Bible; Bible -- Criticism, interpretation, etc; Femmes dans la Bible; Bible -- Critique, interprétation, etc; Bible; Women in the Bible; Criticism, interpretation, etc